Peningkatan Keterampilan Menulis Teks Narasi Menggunakan Model Cooperative Learning Tipe Picture and Picture di Kelas IV SD Pembangunan Laboratorium Universitas Negeri Padang - Handayani, Meri; Azima, Nana Fauzana (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve narrative text writing skills using a picture and picture type cooperative learning model in grade IV of SD Laboratory Development, State University of Padang. This research was carried out in two cycles with the stages of planning, implementation, observation and reflection. The subject of the study is a student in grade IV of SD Laboratory Development, State University of Padang, with data collected through test and non-test techniques, while the research instrument is through test sheets and non-test. The results show that the use of the Picture and Picture Type Cooperative Learning model can significantly improve narrative text writing skills. In the first cycle, the average score in the aspect of the Teaching Module 90 with qualification (A), increased in the second cycle, namely obtaining an average of 95 with qualification (A), so it can be said that learning planning in the form of the Teaching Module cycle I to cycle II has increased. The results of the observation of the teacher aspect and the student aspect of the first cycle of the first meeting obtained the same score, namely 86.11 with good qualifications (B) and increased in the first cycle of the second meeting to 88.88 in the aspect of teachers and students. The average score for teacher and student activities in the first cycle of meetings I and II was 87.49 with a Good qualification (B). Then in the second cycle, scores for teacher activities were obtained 97.22 and student activities were 97.22 with very good qualifications (A).